Financial Analysis of AstraZeneca Company (Finanční analýza společnosti AstraZeneca) - Maidaniuk, Varvara; Nohýnková, Barbora; Hrdý, Milan; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2025)
This bachelor's thesis focuses on the financial analysis of the AstraZeneca company. The thesis aims to assess the company's financial health and compare it to other companies within the same branch. Financial analysis is carried out based on the annual reports from 2019 to 2023. In the first part, AstraZeneca and its competitors are described. Financial analysis is then conducted, including calculating absolute indicators and ratio analysis. Afterwards, strategic analysis with internal and external potential analysis is conducted. The conclusion includes an AstraZeneca company financial health evaluation.
Vedoucí práce: Barbora Nohýnková
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: účetnictví a finanční řízení podniku [obor bakal. práce]; bakalářské práce; bachelor's theses